The Assessment, Benefits and Delivery of Physical Activity in People with Schizophrenia: A Survey of Members of the International Organization of Physical Therapists in Mental Health. (1st May 2014) - Stubbs, Brendon; Soundy, Andy; Probst, Michel; De Hert, Marc; De Herdt, Amber; Parker, Anne; Vancampfort, Davy
Abstract Background People with schizophrenia typically die over a decade before members of the general population. Physical activity is a low cost and effective intervention that can have a multitude of beneficial effects on people with schizophrenia. Physical therapists lead in the delivery of physical activity in many of the commonly observed co‐morbidities in schizophrenia, yet their role in the delivery of physical activity in patients with schizophrenia remains unclear. Objective This study aimed to establish an international consensus on physical therapists' beliefs, potential benefits and practices in the use of physical activity in schizophrenia. Method All members of the International Organization of Physical Therapists in Mental Health were invited to take part in a cross‐sectional online survey. All data were analysed using descriptive statistics and quantitative content and/or thematic analysis. Results One hundred and fifty‐one physical therapists from 31 countries responded. Almost all respondents (92%) felt that physical activity benefited patients with schizophrenia, and 75.2% and 22.5%, respectively, felt that it was very important and important that physical therapists oversee in the delivery of physical activity in psychiatric services. Resultant themes established that physical activity has a plethora of beneficial effects on people with schizophrenia including physical health benefits and biopsychosocial effects such as improved mental health, socialization and quality of life. In addition, participants felt they have the necessary theoretical knowledge and clinical skills required for leading and overseeing physical activity programmes in this complex patient group. Conclusion Physical therapists identified that physical activity has a plethora of benefits for patients with schizophrenia and that they have the necessary knowledge and skills to lead and oversee the successful delivery of physical activity in patients with schizophrenia in clinical practice. Copyright © 2014 John Wiley & Sons, Ltd.